(untitled) (Eurasian Journal of Ecology, 2025)
Human economic activity is a key factor shaping the modern landscape. To ensure a high level of environmental well-being, nature conservation, and the rational use of natural resources, it is necessary to comprehensively consider all types of technogenic impacts on the natural environment — both direct and indirect. In this regard, the study of eco-geomorphogenesis under the conditions of anthropogenic pressure and changing climate is especially relevant and becomes one of the priority tasks for maintaining environmental sustainability. This article examines the features of eco-geomorphogenesis in the Kostanay region under the influence of current anthropogenic activities. The processes of landform formation and transformation caused by human activities such as land use, agriculture, forestry, and mineral extraction are analyzed. The consequences of these changes for the natural environment are considered: increased erosion, alteration of the water regime, soil degradation, and disruption of ecosystem stability. Special attention is paid to the interaction between geomorphological and ecological factors in landscape transformation processes. Conclusions are drawn about the current state of geomorphogenetic processes, and measures are proposed to mitigate the negative consequences of anthropogenic impact in the Kostanay region. Keywords: eco-geomorphogenesis, Kostanay region, geology, geomorphology, geological and lithological features.